Chemoreception of Mouthparts: Sensilla Morphology and Discovery of Chemosensory Genes in Proboscis and Labial Palps of Adult Helicoverpa armigera (Lepidoptera: Noctuidae) - Guo, Mengbo; Chen, Qiuyan; Liu, Yang; Wang, Guirong; Han, Zhaojun (Frontiers in Physiology, 2018)
Siphoning mouthparts, consisting of proboscis and labial palps, are the exclusive feeding organs and important chemosensory organs in most adult Lepidoptera. In this study, the general morphology of the mouthpart organs and precision architecture of the proboscis was described in adult Helicoverpa armigera. Three major sensilla types with nine subtypes including three novel subtypes were identified. The novel sensilla styloconica subtype 2 was the only one having a multiporous structure, which may play olfactory roles. For further understanding of the chemosensory functions of mouthpart organs, we conducted transcriptome analysis on labial palps and proboscises. A total of 84 chemosensory genes belonging to six different families including 4 odorant receptors (ORs), 6 ionotropic receptors (IRs), 7 gustatory receptors (GRs), 39 odorant binding proteins (OBPs), 26 chemosensory proteins (CSPs), and 2 sensory neuron membrane proteins (SNMPs) were identified. Furthermore, eight OBPs and six CSPs were identified as the novel genes. The expression level of candidate chemosensory genes in the proboscis and labial palps was evaluated by the differentially expressed gene (DEG) analysis, and the expression of candidate chemosensory receptor genes in different tissues was further investigated by quantitative real-time PCR (qRT-PCR). All the candidate receptors were detected by DEG analysis and qRT-PCR, but only a small part of the OR or IR genes was specifically or partially expressed in proboscis or labial palps, such as HarmOR58 and HarmIR75p.1, however, most of the GRs were abundantly expressed in proboscis or labial palps. The reported CO2 receptors such as HarmGR1, GR2, and GR3 were mainly expressed in labial palps. HarmGR5, GR6, and GR8, belonging to the “sugar receptor” clade, were mainly expressed in proboscis or antenna and were therefore suggested to perceive saccharide. The results suggest that the mouthparts are mutually cooperative but functionally concentrated system. These works contribute to the understanding of chemical signal recognition in mouthpart organs and provide the foundation for further functional studies.